Perancangan Sistem Informasi Persediaan Barang Dagangan Dengan Metode Rata-Rata Bergerak - Andriani kusumaningrum (Jurnal Ilmiah SINUS, 2010)
Merchandise inventory using the moving average method can be used to determine the average cost of goods purchase or cost of goods sold in each transaction of purchase or sales..The results of this research is a design of merchandise inventory information system with a moving average method. The design of the system in this research are Data Flow Diagrams, Database Design, the design of input-output and menu scheme (Design Sketch User Interface).Keywords : design, inventory, moving average method